The Influence of Influencer Marketing on Brand Awareness and Sales of Fashion Brands in Indonesia - Mayratih, Siska (West Science Social and Humanities Studies, 2025)
This study examines the influence of influencer marketing on brand awareness and sales in the fashion industry in Indonesia using a quantitative research approach. The analysis was conducted with 170 respondents, utilizing a Likert scale (1-5) and employing Structural Equation Modeling - Partial Least Squares (SEM-PLS 3) for data analysis. Results reveal that influencer marketing has a significant and positive effect on brand awareness and sales. Additionally, brand awareness mediates the relationship between influencer marketing and sales, with a direct positive impact on sales. The study underscores the importance of leveraging influencer marketing strategies to enhance brand awareness and drive sales performance, highlighting its role as a vital marketing tool in the competitive fashion industry in Indonesia.